ANGKATAN LAUT JEPANG DALAM PERANG JEPANG-RUSIA 1904-1905 DAN RELEVANSINYA DALAM PEMBELAJARAN SEJARAH KELAS XI SMA - Astuti, Janah Puji (Candi, 2015)
This research aims at describing: (1) the history of Japanese Navy, (2) the roles of Japanese Navy in the war of Japan-Russia in 1904-1905, (3) the development of Japan Navy after the war of Japan-Russia  in1904-1905, (4) the relevance between the roles of Japanese Navy in the war of Japan-Russia in 1904-1905 and history study in the eleventh grade of Senior High School.The method used in this research is Historical method that is defined as an activity of solving problem by collecting history sources that are relevant to the problems being focused in order to understand past event. The sources may involve primary and secondary sources that can be obtained in library, documents centre, and museum. Based on the research it can be concluded that: (1) Emperor Meiji who is well known with Meiji Restoration implemented wisdom for the development of his economy and military that was then known as watchword Fukoku Kyohei (rich countryandstrong military), (2) through Satsuma clan it was established Japanese Navy following Britain?s system, in 1869 Meiji imperial established Navy academy  (Kaigan Heigakku) in Tsukuji, Tokyo, (3) in 1904-1905 Japan Navy took a part in the war between Japan and Russia ended with Japan?s victory, (4) the Japan?s victory of Russia had effect not only to Japan nation but also the rising of nationalism spreading in the whole of Asia.